2013
DOI: 10.1371/journal.pone.0060719
|View full text |Cite
|
Sign up to set email alerts
|

Induced Collagen Cross-Links Enhance Cartilage Integration

Abstract: Articular cartilage does not integrate due primarily to a scarcity of cross-links and viable cells at the interface. The objective of this study was to test the hypothesis that lysyl-oxidase, a metalloenzyme that forms collagen cross-links, would be effective in improving integration between native-to-native, as well as tissue engineered-to-native cartilage surfaces. To examine these hypotheses, engineered cartilage constructs, synthesized via the self-assembling process, as well as native cartilage, were impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 37 publications
2
53
0
Order By: Relevance
“…Previously, in articular cartilage-neocartilage integration, a tensile test demonstrated lysyl oxidase induced an apparent interfacial stiffness of 1.5 MPa when treated two weeks prior to and during one week of integration [9]. In this study, detected by a pushthrough test, which assesses primarily shear mechanics, an interfacial stiffness of 17 MPa was measured with lysyl oxidase, CuSO 4 and hydroxylysine treatment, following eight weeks integration.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Previously, in articular cartilage-neocartilage integration, a tensile test demonstrated lysyl oxidase induced an apparent interfacial stiffness of 1.5 MPa when treated two weeks prior to and during one week of integration [9]. In this study, detected by a pushthrough test, which assesses primarily shear mechanics, an interfacial stiffness of 17 MPa was measured with lysyl oxidase, CuSO 4 and hydroxylysine treatment, following eight weeks integration.…”
Section: Discussionmentioning
confidence: 63%
“…During collagen formation and repair, lysyl oxidase oxidizes amino groups on collagen's lysine residues to form reactive aldehydes, which react with others, condensing to form covalent pyridinoline cross-links [20], a reaction that is dependent upon molecular oxygen and copper ion. Previously, lysyl oxidase has been shown to enhance collagen cross-links towards improving integration of neocartilage and native hyaline cartilage [9]. Following two weeks integration in vitro, lysyl oxidase induced 2-2.2 times increase in apparent stiffness across the cartilage interface in both neocartilage-to-native cartilage and native-to-native cartilage interfaces [9].…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] These results support the value of strategies using exogenous treatments such as lysyl oxidase to strengthen the collagen network by increasing collagen cross-link precursors and to prevent the swelling evident in this study. 44 In prior studies of this model system, 45 it had been suggested that the higher deposition of GAG might inhibit collagen deposition, possibly due to a steric effect. Histological stains from this study support this hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Increased neocartilage-to-native cartilage interfacial properties, such as tensile stiffness and strength, were observed after LOX treatment. Longer durations of treatment resulted in statistically higher interfacial tensile properties, 2.2 times that of the untreated control [100].…”
Section: Lox-mediated Enhancement Of Cartilage Integrationmentioning
confidence: 85%